Independent DEM of Antarctica Using GNSS‐R Data From TechDemoSat‐1. Issue 12 (21st June 2018) - Cartwright, Jessica; Clarizia, Maria Paola; Cipollini, Paolo; Banks, Christopher J.; Srokosz, Meric
Abstract: The first digital elevation model (DEM) of the Antarctic ice sheet derived from Global Navigation Satellite Systems‐Reflectometry (GNSS‐R) data from the UK TechDemoSat‐1 satellite is presented. This is obtained using 32 months of data from the mission. This opportunistic and inexpensive method is shown to produce encouraging results from the technology demonstration platform of TechDemoSat‐1, with median bias under 18 m and root‐mean‐square difference under 91 m when compared to the CryoSat‐2 1‐km DEM v1.0. Discrepancies between the two data sets are explored along with possible causes of such differences and potential improvements to further optimize this technique for future GNSS‐R missions. Plain Language Summary: Obtaining measurements of the Antarctic ice sheet is critical for understanding the effects that climate change might be having on it and its potential future contribution to rising sea levels. The only practical way to do this is by using satellite data, and this has been done successfully previously from the CryoSat‐2 satellite, which carries a radar altimeter. However, due to its orbit, it cannot measure an area near the South Pole. Here we demonstrate that measurements of the Antarctic ice sheet, including the vicinity of the South Pole, can be made by taking advantage of GPS signals that bounce off the ice sheet surface. The data are obtained from the UK's TechDemoSat‐1 mission, which carries a simple low‐cost receiver to pick up the reflected GPS signals. The results from this demonstration mission (which was not designed to survey ice sheets) are promising, showing the potential of this approach for measuring the ice sheet in the future with a dedicated satellite mission. Key Points: Altimetry over glacial ice from satellite GNSS‐Reflectometry is presented for the first time over the extent of the Antarctic continent Elevation of the ice is estimated from GNSS‐R data from the TechDemoSat‐1 satellite Good agreement is observed with CryoSat‐2 1‐km DEM  v1.0